ANALISIS RASIO TREND KEMANDIRIAN KEUANGAN DAERAH OTONOM PROPINSI SULAWESI SELATAN TAHUN 2005 – 2007 - Amirullah Amirullah (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2012)
The research method used in this study is a quantitative method of trend analysis. The results of the discussion was the financial independence of the autonomous counties / cities in South Sulawesi province in 2004 until the year 2007 as the Autonomous Region counties / cities in South Sulawesi province in the period in the category of financial independence is very low. And in the category of instructive relationship patterns, namely the role of the central government is more dominant than the independence of local governments. Trend Luwu financial independence, and the District Pinrang him very well with a static trend in the range of financial independence above 100% with compared to other districts. In 2007, compared with base year 2004, the trend of financial independence autonomous county / city in South Sulawesi province increase, the District of Bone and Sinjai.